Navigating food environments for complementary feeding in the drylands of northern Kenya - Patricia J. Kiprono; Jennifer Kaiser; Hussein T. Wario; Waliou Amoussa Hounkpatin; Brigitte A. Kaufmann (Food Security, 2025)
Despite numerous studies and aid programs, child malnutrition in African drylands remains a critical challenge for child growth and development. Although mothers are central to children's nutritional well-being, their perspectives are rarely prioritized. We seek to understand mothers' decision-making for feeding their children within the specific contexts of their personal food environments, including socioeconomic constraints and environmental conditions. Specifically, we analysed the influence of these constraints and conditions between locations and ethnic communities in Marsabit County, northern Kenya. We used a participatory approach for qualitative data collection to compare the extent to which women's personal food environments influence child-food provision among Rendille (pastoral), Borana (agro-pastoral), and Burji (crop-farming) communities. In 18 focus group discussions conducted in 2021–2022, women caregivers in six groups in these three communities rated and discussed up to 35 foods according to accessibility, affordability, convenience, healthiness, and acceptance by children. Mothers' perspectives on food characteristics associated with personal food environment factors vary depending on their contextual conditions. The ratings of food items according to these factors differed between the pastoral and agro-pastoral communities. The concepts of the food environment show how various factors affect mothers' food choices and child nutrition. These factors include location, livelihood systems, seasonality, infrastructure, household conditions, and food cultures. Therefore, food environment framing provides better strategies to inform interventions that aim to promote healthy and sustainable diets to improve children's nutrition and well-being.
Keywords: 630; Child feeding; Food security; Mothers; Food choices; (agro-)pastoralists; Tropentag 2023